Influence of reinforcement and processing on aluminum matrix composites modified by stir casting route. (20th December 2019) - Rozhbiany, Fakhir Aziz Rasul; Jalal, Shawnim Rashied
In the present study, the individual and combined effect of reinforcement on aluminum (Al; 6063) alloy is discussed. These Al metal matrix composites with individual and multiple reinforcements are finding increased application in aerospace, automobile industry, underwater machines, and transportation application, due to improved mechanical and tribological properties like strong, stiff, wear, and impact resistance. Al 6063 alloy reinforced with different elements such as two types of ceramic mortar ash (MA) and nanofibrillated composite (NFC), industrial waste met coke ash (MCA), and agro waste straw ash with the constant rate of 5 wt% for each reinforced element. The results show a significant effect on the mechanical properties such as tensile strength and hardness. Damping characteristic improved by mixing of MA and NFC together and the results shown that the damping characteristics can be good for MCA reinforcement. Logarithmic decrement slowly increased by adding all types of reinforced metal together. NFC has high resistance to wear loss followed by MA and MCA but for mixing all types of reinforcements together resulted in good improvement in wear loss. Microstructure analysis of Al matrix composites is the small grain size and uniform distribution with good particulate matrix interface bonding.